The risks and characteristics of the delayed bleeding after endoscopic submucosal dissection for early gastric carcinoma in cases with anticoagulants. (2nd October 2020) - Saito, Hiroaki; Igarashi, Kimihiro; Hirasawa, Dai; Okuzono, Toru; Suzuki, Kenjiro; Abe, Yoko; Nawata, Yoshitaka; Tanaka, Yukari; Tanaka, Ippei; Unno, Shuhei; Nishikawa, Yoshitaka; Tsubokura, Masaharu; et al.
Abstract: Background: Endoscopic submucosal dissection (ESD) is a minimally invasive treatment for early gastric carcinoma. Vitamin K antagonists and direct oral anticoagulants (DOAC) were reported to increase the risk of delayed bleeding after ESD. However, the evaluation of ESD cases taking anticoagulants is scarce. We analyzed the risk and characteristics of delayed bleeding after gastric ESD in patients on anticoagulants. Methods: We performed a retrospective observational study at a single center. Consecutive patients who underwent ESD for early gastric carcinoma and took anticoagulants, including warfarin, rivaroxaban, dabigatran, apixaban, and edoxaban, between January 2012 and December 2018, were analyzed. We also calculated delayed bleeding rates for those without anticoagulants. Results: Of 1855 eligible patients who underwent gastric ESDs, 143 took anticoagulants. Delayed bleeding occurred in 30 (21.0%) cases taking anticoagulants, with 15 (19.5%) cases in the DOAC group [rivaroxaban, seven cases (21.2%); dabigatran, four cases (20.0%); apixaban, four cases (23.5%); and edoxaban, zero cases (0%)] and 15 cases (22.7%) in the warfarin group. Furthermore, 43/344 (12.5%) patients taking antiplatelets and 76/1368 (5.6%) patients without antithrombic drugs experienced delayed bleeding. Multivariable logistic analysis revealed post-heart valve replacement (OR, 6.56; 95% CI, 1.75–24.7; p  < .05) as a risk for delayed bleeding in warfarin-taking patients, while no statistically significant factor was found in DOAC-taking patients. Conclusions: Anticoagulants were associated with a high incidence of severe delayed bleeding. Careful attention should be paid to patients on anticoagulants after gastric ESD, especially those on warfarin after heart valve replacement.